RELATIONSHIP BETWEEN STRESS WITH SLEEP QUALITY IN ELDERLY - Sucipto, Sucipto; Rinawati, Fajar (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2020)
ABSTRACTAging is a physiological process that starts from birth. This inevitable biological process includes health, social, cultural and economic dimensions. Elderly people will experience several changes in physiological functions that affect physical and psychological conditions. Increase and decrease in the elderly nervous system, will cause the elderly to experience health problems, one of which is a sleep disorder.Objective: This study aims to determine the relationship of stress with sleep quality in the elderly in Pondok Lansia An Nur and Posbindu Dharma Husada Insan Mandiri (DHIM) Balowerti Kota Kediri.Method: This research is a descriptive correlation study, with a cross sectional approach Test the results of research data using chisquare. The number of samples is 20 people.Results: there was a significant relationship between stress and sleep quality in the elderly with a p value of 0,000 (P <0.05).Discussion: This research is expected to be used as basic data for further research, namely measures of stress management and sleep improvement therapy, which are expected to improve the quality of life of the elderly. Keywords: Stress, sleep quality, elderly